Wireless sensor network in civil engineering application - Ong, Bang Hui. (2009)
Strain is one of the important physical quantities used to judge the health of a structure; conventional strain sensors have limited measuring capability and not necessarily optimized for civil infrastructure applications. Therefore this proposed project is to develop an application of real time Vibrating-Wire Strain Gauge Network for remote wireless monitoring of both Civil and offshore structures. With this proposed system, users can monitor buildings from any place in the world, as long as there is available internet access.